(untitled) (Nexo Revista Científica, 2020)
In this research, we try to study the sedimentary characteristics and the trend of textural changes in the sediments of the Jajrood River from upstream to downstream at the point of junction to Latiyan dam. Based on the textural changes of sediments along the path from the upstream in the Garmabdar area to the downstream to the Latiyan Dam, the Jajrood River is divided into four A, B, C and D basins. Twenty sediment samples were collected and all sieved by dry and wet method also the specimens were morphoscopically studied. Data from field and laboratory phases were combined and interpreted using reliable scientific sources and finally a detailed summary was obtained regarding sedimentology of the study area. Mineralogically, the sediment type of the river is a clastic carbonate sedimentary type with fragments ranging from 30 to 58 percent and rock fragments between 25 to 50 percent abundance. Other minerals, such as feldspar minerals, account for about 1 to 4 percent, quartz 5 to 10 percent, and opauqe minerals from 1 to 5 percent. Examination of the average particle size in the A to D basins shows that decreasing trend of sediment size from the A to C basin occurs and reverses in the D basin. In the first three basins, the sorting grade of the river sediments is very bad and in the last basin it has become extremely bad. The amount of kurtosis of the particle distribution curve from upstream to downstream of the river is generally increasing trend. Textural changes along the river do not follow natural conditions due to the influence of various natural factors such as the entry of distributary into the main River, and phenomena such as landslide and rock collapses and debris flows, especially during floods along the riverbank.